Crime reporting practices among traders at Alaba International Market, Lagos - Ayodele Johnson (Temida, 2018)
In the field of contemporary study of victims in most developing countries worldwide, the reporting of personal victimization has received more attention by scholars than business victimization. Therefore, the aim of the current study is to examine the influence of business crimes reporting practices among traders on the development of the Alaba International Market, the traders and national economy. The study was conducted between October 3 and 8, 2015, in Lagos, Nigeria. It collected quantitative data from 245 respondents that were randomly selected from traders at the market. These were complemented by qualitative data collected through In-depth Interviews and Focus Group Discussions with purposively selected participants. The data were analyzed. The quantitative data found that 82.1% of the respondents attributed the victimization of small businesses to organized crimes by youth. The qualitative data indicated that the Alaba Market investors will reduce the unemployment rate in Lagos if the government stop frustrating the traders with the tax burden. The study concluded that business crimes prevent economic development. It suggests partnership among stakeholders for the provision of closed-circuit television cameras to prevent business violence and induce economic development at Alaba International Market.